Embracing international human rights law: the Malaysian experience in navigating the dual quality of international law - Shuaib, Farid Sufian (IIUM Press, International Islamic University Malaysia, 2019)
International human rights law, as with the setting up of the United Nations at the end of the Second World War, promises the dignity and worth of the human person of nations large and small. International human rights law is supposed to save the world population from the scourge of war, despots and other miseries. The international legal order after the end of the Second World War also promises equal sovereignty where all states are equal under international law in spite of inequality of population size, resources and military might. International human rights law thus applies to all states, to protect all populations. International human rights law has been used to liberate colonies and to protect people from oppression. The universal nature of international human rights law means that it applies to all nations large and small. However, the very fact that it is universal is also troublesome when in its application, the Eurocentric understanding of human rights is imposed on all. This article looks both at the acceptance of Malaysia of international human rights law and her schemes in determining the place for universalism in the application of the law.